2019
DOI: 10.35467/sdq/115539
|View full text |Cite
|
Sign up to set email alerts
|

The impact of crime on security in tourism

Abstract: Objectives: Tourism has become one of the main economic sectors of the 21st century. Today, tourism is facing various security threats such as terrorism, crime and potential armed conflicts, and the most common security threat to tourism is crime. The aim of this paper is to analyse how crime affects security in tourism and to describe the consequences of crime for tourism. Methods: A descriptive method was used in this paper to explain the concept of security in tourism and to analyse the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…Extant literature indicated a significant relationship between tourist victimization and SnS in the context of tourism (Baker and Stockton, 2014;Boakye, 2012;Brunt et al, 2000;Lisowska, 2017). Matakovic and Cunjal-Matakovic (2019) identified four patterns of crime victimisation within the tourism literature. These include tourism and crime rates (De Albuquerque and McElroy, 1999;Johnny and Jordan, 2007), relationship between tourism, crime and socio-economic indicators (Biagi et al, 2012;Palanca-Tan et al, 2015).…”
Section: Tourist Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature indicated a significant relationship between tourist victimization and SnS in the context of tourism (Baker and Stockton, 2014;Boakye, 2012;Brunt et al, 2000;Lisowska, 2017). Matakovic and Cunjal-Matakovic (2019) identified four patterns of crime victimisation within the tourism literature. These include tourism and crime rates (De Albuquerque and McElroy, 1999;Johnny and Jordan, 2007), relationship between tourism, crime and socio-economic indicators (Biagi et al, 2012;Palanca-Tan et al, 2015).…”
Section: Tourist Victimizationmentioning
confidence: 99%
“…This is because they carried foreign currencies, credit cards and personal belongings such as mobile phones, cameras, wrist watches, etc. Other studies have found that tourists became victims because of their country of origin and their way of dressing (Matakovic and Cunjal-Matakovic, 2019). Other tourists were seen to be careless and indulged in anti-social and selfdestructive behaviours, such as drug consumptions and prostitutions (De Albuquerque and McElroy, 1999).…”
Section: Tourist Victimizationmentioning
confidence: 99%
“…The author further substantiates that tourists prioritize security issues when making a vacation choice as the majority of them are derive total satisfaction from positive aspects of life. Indeed, much attention should be given to the safety of the tourists so as to attract both domestic and international tourists (Mataković and Mataković, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Mataković and Cunjak Mataković (2019), crime affects tourism at two observable levels-the micro level and the macro level. At the latter, this refers to crime disturbing society in general, the social community and/or a particular tourist destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of the negative effects associated with elevated crime at tourist destinations, both travel and security in tourism cannot be taken for granted. Therefore, it is necessary to make significant efforts to ensure a safe environment for tourists (Mataković and Cunjak Mataković 2019)-hence, the importance of TOP units and evaluations of TOP training.…”
Section: Literature Reviewmentioning
confidence: 99%